Whole Exome Sequencing Identifies a Novel Predisposing Gene, MAPKAP1, for Familial Mixed Mood Disorder - Yang, Chunxia; Li, Suping; Ma, Jack X.; Li, Yi; Zhang, Aixia; Sun, Ning; Wang, Yanfang; Xu, Yong; Zhang, Kerang (Frontiers in Genetics, 2019)
Background: Mood disorder is ranked seventh among the worldwide causes of non-fatal disease burden and is generally believed to be a heritable disease. However, there is still a substantial portion of the heritability yet to be discovered, despite the success of genome-wide association studies for mood disorder. A proportion of the missing heritability may be accounted for by coding variants segregating in families enriched with mood disorder. Methods: To identify novel variants segregating with mood disorder, we performed whole-exome sequencing on genomic DNA for a multigenerational family with nine members affected with mood disorder. We prioritized potential causal variants within the family based on segregation with mood disorder, predicted functional effects, and prevalence in human populations. In addition, for the identified variant, we conducted validation in vivo to explore the pathogenesis of mood disorder. Results: We identified and ranked 26 candidate variants based on their segregation pattern and functional annotations. The top-ranked variant, rs78809014, is located in intron 7 of the MAPKAP1 gene. The expression levels of MAPKAP1 in both MDD patients peripheral blood and depressive-like mice ventral dentate gyrus were significantly higher than that in controls. In addition, the expression level of MAPKAP1 were correlated with antidepressant response. Conclusions: Although the exact mechanisms in the family remain to be elucidated, our data strongly indicate that a probable role of the variant, rs78809014, in the regulatory process of the expression of MAPKAP1 and thus in the development of mood disorder in familial mood disorder.